Pickering-emulsion-templated synthesis of 3D hollow graphene as an efficient oil absorbent. Issue 7 (21st January 2021) - Pohan, Nurul Aqilah; Wahid, Mohd Haniff; Zainal, Zulkarnain; Ibrahim, Nor Azowa
Abstract : The preparation of graphene in three-dimensional mode represents an alternative method to maintain its characteristically large surface area, which, under normal circumstances, is diminished by the restacking of the individual sheets. Abstract : The preparation of graphene in three-dimensional mode represents an alternative method to maintain its characteristically large surface area, which, under normal circumstances, is diminished by the restacking of the individual sheets. Sufficiently stable 3D graphene enables the high surface area characteristic of monoatomic graphene layers to be obtained. Based on the coupling of the high surface area and the void spaces that are thus created, which act as pores, 3D graphene is anticipated to have potential as a sorbent material. In this study, lightweight 3D hollow graphene featuring a unique thin skeletal framework was developed using the Pickering emulsion route for oil absorbent applications. In this technique, toluene droplets stabilized by graphene oxide layers in a water system were used as the template, and upon the removal of the solvent by freeze-drying and microwave-assisted reduction, 3D hollow graphene was obtained. The produced 3D graphene demonstrates excellent sorption efficiencies of 84 to 145 g g −1 for different types of oil and organic solvents in the first absorption. This excellence can be attributed to its multi-level porosity as elucidated by mercury intrusion porosimetry (MIP) and Brunauer–Emmett–Teller (BET) surface area analysis, which indicated a bimodal pore size distribution with macroporosity and mesoporosity and a surface area of 127 m 2 g −1 . The 3D hollow graphene prepared using the Pickering emulsion template technique incorporating microwave treatment can be readily recycled using a solvent extraction process for a total of ten sorption–desorption cycles without significant losses in its efficiency, making it promising for further consideration as an appropriate material for oil spill incidents.